Early detection of gadget addiction in early childhood and its management in the context of early childhood education: Literature review - La Adi, Siska; Maronta, Yusuf; Kasim, Indah Luthfiyah (Arshaka: Social Sciences and Education, 2025)
The use of gadgets among young children is rapidly increasing and poses a risk of addiction that negatively impacts child development. This study aims to identify strategies for early detection and treatment of gadget addiction through a systematic literature review. Articles were searched on Google Scholar and the Education Resources Information Center (ERIC) using keywords such as gadget addiction, early childhood gadget use, screen addiction, and digital parenting. Out of 21 initial articles, 15 met the inclusion criteria (2019-2025) and were analyzed based on early detection, impact, prevention, and management. The results of the study show that gadget addiction is characterized by behavioral changes, excessive use, decreased social interaction, and emotional disturbances. Negative impacts include a decline in language skills, social skills, moral and religious values, and the risk of mental disorders. The role of parents is proven to be dominant through guidance, content supervision, and providing alternative activities. Effective management requires a gradual approach involving the family, teachers, and the environment. These findings emphasize the need for comprehensive efforts to minimize the risk of gadget addiction and support optimal child development.